Determination of Airline Network, Model Choice, Flight Plan and Strategic Alliance, Employee Salary, Number of Air Ground Employees, and Target Passenger towards Quality of Airline Business Type - Atong Soekirman (Dinasti Publisher, 2024)
Literature review research on Airline Network Determination, Flight Model Choice, Flight Plan and Strategic Alliance, Employee Salary, Number of Ground Employees and Passenger Target on Airline Quality is a scientific literature article in the scope of operational management science. The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of operational management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. The data used in this descriptive qualitative approach comes from previous research that is relevant to this study and is sourced from academic online media such as the Scopus Journal, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this article are: 1) Airline network affects airline quality; 2) Flight model choice affects airline quality; 3) Flight plans and strategic alliances affect airline quality; 4) Employee salary affects airline quality; 5) The number of ground employees affects airline quality; and 6) Passenger target affects airline quality.